Math, asked by bajajpriyanka, 5 days ago

Solve the pair of equations:​

Attachments:

Answers

Answered by Zahrah2008
1

Answer:

2x+3y=13

2x+3y=13y=

2x+3y=13y= 3

2x+3y=13y= 313−2x

2x+3y=13y= 313−2x

2x+3y=13y= 313−2x

2x+3y=13y= 313−2x Substitute the value of y in equation (2):

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=23

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5(

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 3

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=23

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=69

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−65

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=13

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=134+3y=13

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=134+3y=133y=13−4

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=134+3y=133y=13−43y=9

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=134+3y=133y=13−43y=9y=3

2x+3y=13y= 313−2x Substitute the value of y in equation (2):4x+5y=234x+5( 313−2x )=2312x+65−10x=692x=69−652x=4x=2Then substitute the value of x in equation (1):2(2)+3y=134+3y=133y=13−43y=9y=3Therefore solution is x=2 ans y=3

Step-by-step explanation:

Helps you

Answered by itzrj
1

Step-by-step explanation:

Let 1/x be u and 1/y be v

Now, we have

2u+3v=13 and,

5u-4v=-2

on solving both equations we get

u = 2 and v = 3

then x = 1/2 and y =1/3

Similar questions